2016
DOI: 10.1371/journal.pone.0149395
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Predictors of Social and Leisure Activity 10 Years after Stroke

Abstract: BackgroundRestrictions in social and leisure activity can have negative consequences for the health and well-being of stroke survivors. To support the growing number of people who are ageing with stroke, knowledge is needed about factors that influence such activity in a long-term perspective.AimTo identify long-term predictors of the frequency of social and leisure activities 10 years after stroke.Method145 stroke survivors in Sweden were followed-up at16 months and 10 years after a first-ever stroke. Data re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 59 publications
7
51
1
Order By: Relevance
“…Almost half of the participants reported unmet needs in relation to fatigue and mobility. These results are in line with previous studies showing that fatigue and mobility problems are common long after the stroke occurred and impact negatively on many aspects of functioning, in particular participation in everyday life [41][42][43][44]. Since rehabilitation targeting mobility can yield beneficial effects [45] even in the chronic phase after stroke [46], our results indicate that there is a need for recurrent long-term rehabilitation.…”
Section: Discussionsupporting
confidence: 92%
“…Almost half of the participants reported unmet needs in relation to fatigue and mobility. These results are in line with previous studies showing that fatigue and mobility problems are common long after the stroke occurred and impact negatively on many aspects of functioning, in particular participation in everyday life [41][42][43][44]. Since rehabilitation targeting mobility can yield beneficial effects [45] even in the chronic phase after stroke [46], our results indicate that there is a need for recurrent long-term rehabilitation.…”
Section: Discussionsupporting
confidence: 92%
“…Participants had an overall good outcome in all of the SIS domains in the present study, regardless of functional dependency, and lowest scores were present in the emotion domain. Perceived emotion has been shown to be associated with perceived participation (33), and in the present study selfperceived participation was lower in participants that were functionally dependent, also seen previously (13,39,40). It could be hypothesised that increased level of participation after stroke also could improve self-perceived outcome.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, many participants in our study perceived problems when bicycling, gardening, participating in sports, or driving a car. It has been shown that driving is a significant factor in the frequency of social and leisure activities after stroke (28) and that involvement in leisure activities is related to how content persons are with their lives (29). Not being able to continue meaningful leisure activities because of sensory impairment of the UL could have a negative impact on a person's well-being and should be considered in rehabilitation.…”
Section: Affected Movement Control and Problems Using The Upper Limb mentioning
confidence: 99%